Enhanced photocatalytic degradation activity for tetracycline under visible light irradiation of Ag/Bi3.84W0.16O6.24 nanooctahedrons1. Issue 11 (21st March 2015) - Li, Xinying; Wang, Liping; Xu, Dongbo; Lin, Jincheng; Li, Ping; Lin, Shuang; Shi, Weidong
<x xml:space="preserve">Abstract</x> In this work, a Ag/Bi3.84W0.16O6.24 nanooctahedron composite photocatalyst was successfully synthesized via a green method at room temperature using silver nitrate (AgNO3) as the silver source.